Curricula and resources related to social entrepreneurship and public health innovation within schools of public health in the United States - Hyde, Ingeborg; Khoshnood, Kaveh; Chahine, Teresa; Basrai, Fatema (Frontiers in Public Health, 2024)
This paper examines the current state of social innovation and entrepreneurship programming, courses, and centers within schools of public health through a survey data analysis. This report presents a cross-sectional survey conducted among faculty members of public health schools in the United States. The survey aims to determine the availability and current state of student-centered programs and courses centered around social innovation and entrepreneurship within schools of public health. Insights were drawn from 19 professionals across 15 schools of public health. Uncertainties surround the sustainability of current programs, with insufficient funding, human resources, and the need to teach more pressing topics identified as the most significant obstacles. Key areas identified as opportunities for growth were faculty engagement, expertise, and funding to expand more structured programming.